2019
DOI: 10.1002/fuce.201900010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Frequency Narrow Pulse Current on the Degradation of Proton Exchange Membrane Fuel Cells

Abstract: Multi‐phase DC/DC converter is widely used in fuel cell vehicles to adjust the voltage. Single phase mode of converter is adopted to increase efficiency when current ripple meets requirement. Therefore, it is necessary to commutate between different phases at low frequency, due to the temperature rising of each phase‐leg. However, narrow pulse current occurs during the phase commutation. Pulse current can cause variations in water and gas content inside the proton exchange membrane fuel cell (PEMFC), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Zhou et al [23] studied the effect of the low-frequency narrow pulse current on the degradation of the proton exchange membrane fuel cells. Their results showed that the narrow pulse current of 4 ms did not affect the life of the fuel cell because there was no gas shortage, the changes in relative humidity and membrane moisture content were less than 1%, and the pressure difference varied within a specified range [26]. As shown in Figure 8, this study focused on the steady-state control system of the fuel cell under the proposed DWM architecture.…”
Section: Results Analysismentioning
confidence: 99%
“…Zhou et al [23] studied the effect of the low-frequency narrow pulse current on the degradation of the proton exchange membrane fuel cells. Their results showed that the narrow pulse current of 4 ms did not affect the life of the fuel cell because there was no gas shortage, the changes in relative humidity and membrane moisture content were less than 1%, and the pressure difference varied within a specified range [26]. As shown in Figure 8, this study focused on the steady-state control system of the fuel cell under the proposed DWM architecture.…”
Section: Results Analysismentioning
confidence: 99%